2018
DOI: 10.1007/s11255-018-1858-1
|View full text |Cite
|
Sign up to set email alerts
|

Elevated visceral obesity quantified by CT is associated with adverse postoperative outcome of laparoscopic radical nephrectomy for renal clear cell carcinoma patients

Abstract: Elevated visceral obesity by VFA is associated with increased surgical complexity, postoperative morbidity, postoperative stay and hospitalization expenses for RCCC patients and may be superior to BMI for renal cancer outcome assessment. VFA may be a useful index for the evaluation and calculation of RCCC aggressiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 24 publications
1
29
1
2
Order By: Relevance
“…Obesity increases the risk inherent to major gastrointestinal surgeries [33] and is a confounding risk factor for surgical morbidity in patients undergoing pancreatic resection [15,34]. More precisely, visceral obesity is a major factor that increases postoperative complications [35,36]. Difficult manipulation, poor laparoscopic view, prolonged operative time, and the presence of a fatty or friable pancreas are related to visceral obesity and can be risk factors for postoperative complications [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity increases the risk inherent to major gastrointestinal surgeries [33] and is a confounding risk factor for surgical morbidity in patients undergoing pancreatic resection [15,34]. More precisely, visceral obesity is a major factor that increases postoperative complications [35,36]. Difficult manipulation, poor laparoscopic view, prolonged operative time, and the presence of a fatty or friable pancreas are related to visceral obesity and can be risk factors for postoperative complications [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…29 Compared with BMI, body fat composition (such as VFA, SFA, and TFA), as a quantitative method by CT image, has recently been focused on its contributions to the progression of RCC. 6,7 However, the relationship between body fat composition and tumor progression and patients' survival still failed to reach an agreement in different disease stages. Zhu et al reported a positive correlation between the percentage of visceral adipose tissue and the Fuhrman tumor grade in patients with T1a RCC.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Over the last decade, obesity has been shown to be associated with increased renal cell carcinoma (RCC) risk and the prognosis of patients. [5][6][7] Body fat accumulation, as one of the important parameters of obesity, which could be measured from a routine computed tomography (CT) image, has recently shown its contribution to the survival of RCC patients. [8][9][10] Several studies have suggested that visceral fat accumulation (VFA) be involved in the prognostic risk stratification.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that corporeity may influence short‐term surgical outcomes in addition to surgical techniques and perioperative care protocols. Recent studies have emphasized the influence of visceral obesity on perioperative and short‐term postoperative outcomes in patients surgically treated . Body mass index (BMI), considered as a conventional tool to assess obesity, can be easily calculated, but it cannot estimate body fat distribution accurately .…”
Section: Introductionmentioning
confidence: 99%